COMMUNICATING IN FOREIGN LAND: CULTURAL SHOCK EXPERIENCES DURING INTERNATIONAL COMMUNITY SERVICE PROGRAM: A CASE STUDY IN THAILAND - Isrina Septiana; Movi Riana Rahmawanti (LPPM UIKA Bogor, 2020)
This study to investigate culture shock experiences faced by Indonesian university students during international community service program in southern Thailand. The participants of this research were five students of seventh semester who had completely conducted community service program in Thailand for about five months. They were Indonesian students of one private university in Bogor. The result of this study revealed that there were three aspects of students’ culture shock faced by Indonesian Students University during international community service program. Those were language, cultural differences and social-academic attitudes. And also the students’ strategies to deal with their culture shock were social support and accepting different cultural.